INTEGRATION OF THE HISTORY OF MATHEMATICS IN GEOMETRY LEARNING: SYSTEMATIC REVIEW - Silmy Ramadhani; Fajri Farid; Manmeet Kaur (Hipotenusa Journal of Research Mathematics Education (HJRME), 2025)
This study aims to examine the integration of the history of mathematics in geometry learning with a systematic review. The method used is descriptive analysis by analyzing 7 related journal articles (2015-2024) indexed in Google Scholar. Data analysis was carried out using VOSviewer software version 1.6.18 for graphical bibliometric mapping. The results of the study indicate the importance of integrating the history of mathematics in geometry learning to enrich students' understanding of geometric concepts. Learning models such as the use of historical examples, analysis of ancient manuscripts and exploration of the contributions of previous mathematicians can increase students' awareness and appreciation of the development of mathematics. Therefore, it is recommended for teachers to integrate the history of mathematics in geometry learning to create a more comprehensive and meaningful educational experience.